2022
DOI: 10.1021/acsami.2c16774
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Blood-Derived Hybrid Hydrogels as Multichannel Microenvironment Modulators for Augmented Bone Regeneration

Abstract: Autologous blood-derived protein hydrogels have shown great promise in the field of personalized regenerative medicine. However, the inhospitable regenerative microenvironments, especially the unfavorable immune microenvironment, are closely associated with their limited tissue-healing outcomes. Herein, novel immunomodulatory blood-derived hybrid hydrogels (PnP-iPRF) are rationally designed and constructed for enhanced bone regeneration via multichannel regulation of the osteogenic microenvironment. Such doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
10
2
Order By: Relevance
“…Therefore, it can be speculated that the blocking effect via PRF infiltration should be more significant than that of the original blood clot. In addition, the platelets within PRF can release multiple immune-related cytokines, such as tumor growth factor β, platelet-derived growth factor, and insulin-like growth factor 1, further optimizing the immune microenvironment and promoting the regenerative process. Moreover, the surface functionalization method also showed application prospects.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that the blocking effect via PRF infiltration should be more significant than that of the original blood clot. In addition, the platelets within PRF can release multiple immune-related cytokines, such as tumor growth factor β, platelet-derived growth factor, and insulin-like growth factor 1, further optimizing the immune microenvironment and promoting the regenerative process. Moreover, the surface functionalization method also showed application prospects.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Then freezedried hydrogels were subjected to complete ethanol permeation through immersion in ethanol in a vacuum chamber and weighed (W 1 ). The porosity of hydrogels was calculated as (W 1 − W H )/ρV H × 100% [ρ is the density of ethanol (0.789 g/cm 3 )].…”
Section: Porosity Analysismentioning
confidence: 99%
“…Growth factors are necessary for bone regeneration, which play vital roles in orchestrated angiogenesis and osteogenesis processes in bone healing . Recent studies have focused on the utilization of autologous growth factors from platelet concentrates for enhanced bone regeneration. As the second generation of platelet concentrates, platelet-rich fibrin (PRF) is strictly autologous and has been frequently used as an alternative for growth factors in clinic and tissue engineering. , Several key growth factors of PRF, including the transforming growth factor β1 (TGF-β1), vascular endothelial growth factor (VEGF), and platelet-derived growth factor (PDGF), can induce cell migration, proliferation, vascularization, and differentiation . According to the previous studies, PRF showed a beneficial effect on bone tissue regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, these hydrogels exhibit diagnostic and therapeutic functionality for treating pathological bone defects [ 26 ]. In addition to providing structural support, the smart hydrogels implanted into bone defects also activate osteogenesis- and immune-related signaling pathways, which regulate multiple cellular behaviors in the bone microenvironment, thereby promoting bone regeneration [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%